2015
DOI: 10.1007/s12550-015-0231-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plastic mulching on mycotoxin occurrence and mycobiome abundance in soil samples from asparagus crops

Abstract: Plastic mulching (PM) is widely used in modern agriculture because of its advantageous effects on soil temperature and water conservation, factors which strongly influence the microbiology of the soil. The aim of this study was to assess the effect of PM on mycotoxin occurrence in relation with mycobiome abundance/diversity and soil physicochemical properties. Soil samples were collected from green (GA) and white asparagus (WA) crops, the last under PM. Both crops were cultivated in a ridge-furrow-ridge system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 49 publications
1
20
2
Order By: Relevance
“…In this study, soil microbial community composition was not significantly altered by mulch type. This is in contrast to other studies that have reported altered bacterial communities in soils under BDMs (Koitabashi et al, 2012;Li et al, 2014b;Muroi et al, 2016), and under non-biodegradable plastic mulches (Farmer et al, 2017;Munoz et al, 2015). Such opposite findings could be due to differences in methodology: For example, the studies by Koitabashi et al (2012) and Muroi et al (2016) were shorter laboratory incubation studies in controlled conditions (28 • C to 30 • C), used pure polymer feedstock rather than commercial film formulations which include plasticizers and other additives, and relied on different detection methods such as polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, soil microbial community composition was not significantly altered by mulch type. This is in contrast to other studies that have reported altered bacterial communities in soils under BDMs (Koitabashi et al, 2012;Li et al, 2014b;Muroi et al, 2016), and under non-biodegradable plastic mulches (Farmer et al, 2017;Munoz et al, 2015). Such opposite findings could be due to differences in methodology: For example, the studies by Koitabashi et al (2012) and Muroi et al (2016) were shorter laboratory incubation studies in controlled conditions (28 • C to 30 • C), used pure polymer feedstock rather than commercial film formulations which include plasticizers and other additives, and relied on different detection methods such as polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE).…”
Section: Discussioncontrasting
confidence: 99%
“…Characterizing the soil microbial communities under the different biodegradable mulches and non-biodegradable PE mulch revealed no significant effect of mulch type on bacterial community structure. This is in contrast to other studies that have reported altered bacterial communities in soils under BDMs (29, 40, 41), and under non-biodegradable plastic mulches (42, 43). Such opposite findings could be due to differences in methodology: for example, the studies by Koitabashi et al (40) and Muroi et al (41) were shorter laboratory incubation studies in controlled conditions (28 to 30°C), used pure polymer feedstock (rather than commercial film formulations which include plasticizers and other additives) and relied on detection methods such as polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies mainly focused on the impacts of PFM on soil moisture, soil structure, soil nutrition and crop yield, while their influences on the soil micro-ecological environment and the evolution of soil microbial community were neglected 9 . Just as different groups of microorganisms vary in their ability to adapt to the various soil environmental conditions, changes on soil microbiology under PFM application are expectable 10 . Li et al .…”
Section: Introductionmentioning
confidence: 99%